(untitled) (Journal of Medicine, 2026)
Background: Hepatitis A virus (HAV) typically causes self-limiting acute hepatitis. However, in individuals with chronic hepatitis B virus infection, HAV superinfection can lead to severe, life-threatening liver complications. Identifying hepatitis B carriers immune to HAV is therefore vital for clinical management and preventive healthcare strategies. Objective: To determine the seroprevalence of anti-HAV IgG in chronic hepatitis B patients. Methods: This observational cross-sectional study was conducted in the Department of Medicine, Comilla Medical College Hospital, from January to June 2021. Using purposive sampling, 84 chronic hepatitis B patients were enrolled. Data were collected via a structured questionnaire, and anti-HAV IgG status was determined using a competitive ELISA technique. Statistical analysis was performed with SPSS. Results: Among 90 chronic hepatitis B patients (75 male,15 female),the overall anti-HAV IgG seroprevalence was 72.2% (65/90), with no significant gender disparity. Contrary to established patterns, the highest prevalence was observed in the youngest age group. Seropositivity was also higher among individuals with illiteracy and those from lower socioeconomic backgrounds. Conclusion: As no age group is fully immune to HAV and HAV superinfection in Chronic Hepatitis B patients can lead to fulminant hepatic failure,so every patient with Chronic Hepatitis B should be screened for HAV, and immunization should be done against HAV, if not already immunized. J MEDICINE 2026; 27(1): 11-15